2014
DOI: 10.1016/j.injury.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of the syndesmotic screw and their effect on functional outcome following acute distal tibiofibular syndesmosis injury

Abstract: Overall, the functional outcome of acute syndesmotic injuries treated with a syndesmotic screw was good and mainly influenced by patient and fracture characteristics. Most different technical aspects of placement appeared not to influence these results. Only screw placement above 41 mm negatively influenced outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 49 publications
0
66
0
8
Order By: Relevance
“…A recent study by Schepers et al showed lower scores on OMAS and AOFAS-AHS when both malleoli were affected [22]. Patients who sustained a Weber C fracture showed a better function than the B type after a median follow-up of 51 months.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study by Schepers et al showed lower scores on OMAS and AOFAS-AHS when both malleoli were affected [22]. Patients who sustained a Weber C fracture showed a better function than the B type after a median follow-up of 51 months.…”
Section: Discussionmentioning
confidence: 89%
“…148,160 Although diabetes mellitus and smoking did not show an effect on loss of syndesmosis reduction, obese patients were 12 times more likely to lose reduction than were patients with a normal body mass index 166 and had poorer functional outcomes. 123 Wukich and Kline 167 found that patients with complicated diabetes were 3.4 times more likely to have soft-tissue and bony complications than patients with uncomplicated diabetes, without considering specifically syndesmotic injuries.…”
Section: Patient Factorsmentioning
confidence: 89%
“…147 Screw placement more than 4.1 cm above the joint negatively influences patient outcomes, likely due to decreased stability at this level or by slight bending of the fibula on insertion, causing widening at the mortise. 148 All evidence regarding orientation of the fixation is from cadaveric and anatomic studies. Anatomically, the fibula sits posteriorly in the tibia, and screws should therefore be directed 30 anteriorly.…”
Section: Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…[67] Üç ve dört korteks gönderilen vidalar arasında uzun dönemde işlevsel fark olmadığını gösteren pek çok yayın vardır. [64,68,69] Dört korteks vida göndermenin bir teorik avantajı, vidanın kırıldığı durumlarda mediyalden ulaşıp çıkarılabilmesidir.…”
Section: Kroni̇k Si̇ndesmoz Yaralanmalariunclassified